Integrated Model of Development of Environmental Moral Competence of Students - Hamrakulov Jahongir Bahtiyorovich (Universitas Muhammadiyah Sidoarjo, 2023)
The article deals with the step-by-step implementation of the development of environmental moral competence in students, the main difference between the concept of competence and other related concepts. The educational process will also cover the development of students' responsibility for the environment and ecological environment through environmental knowledge, skills and abilities.